Kwaito's Promise: Music and the Aesthetics of Freedom in South Africa. Gavin Steingo. 2016. Chicago and London: University of Chicago Press. 23 bw figures (maps, transcriptions and photos), 2 tables, bibliography, filmography, index, 327pp. - Thram, Diane (International Library of African Music, 2017)
pages: 164-166
Keywords: South Africa; African Music